2016
DOI: 10.1093/neuonc/now129
|View full text |Cite
|
Sign up to set email alerts
|

miR-423-5p contributes to a malignant phenotype and temozolomide chemoresistance in glioblastomas

Abstract: Background Gliomas are based on a genetic abnormality and present with a dismal prognosis. MicroRNAs (miRNAs) are considered to be important mediators of gene expression in glioma tissues. Methods Real-time PCR was used to analyze the expression of microRNA-423-5p (miR-423-5p) in human glioma samples and normal brain tissue. Apoptosis, cell cycle, proliferation, immunostaining, transwell, in vitro 2D and 3D migration, and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 29 publications
2
92
0
5
Order By: Relevance
“…26 In gliomas, miR-423-5p is reportedly overexpressed in Chinese primary glioblastomas 27 and contributes to the malignant phenotype as well as TMZ chemoresistance. 11 However, the expression and function of miR-423-5p in GSCs have remained unknown. In this study, we confirmed that miR-423-5p is overexpressed in primary GSCs compared with corresponding primary glioma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…26 In gliomas, miR-423-5p is reportedly overexpressed in Chinese primary glioblastomas 27 and contributes to the malignant phenotype as well as TMZ chemoresistance. 11 However, the expression and function of miR-423-5p in GSCs have remained unknown. In this study, we confirmed that miR-423-5p is overexpressed in primary GSCs compared with corresponding primary glioma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Li et al [38] showed that miR-423-5p expression was increased in gliomas tissues and ecoptic expression of miR-423-5p increased glioma cell angiogenesis, proliferation and invasion through targeting ING-4. Lu et al [39] demonstrated that serum miR-423-5p was upregulated in the stage I-II colorectal cancer patients compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐423‐5p is previously reported to be aberrantly expressed in several cancers and could promote the proliferation and invasion of gastric cancer cells by downregulating the expression of trefoil factor 1 (TFF1) . However, whether miR‐423‐5p is enriched in the circulating exosomes of gastric cancer patients and the functional roles of exosomal miR‐423‐5p in gastric cancer have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%